Magnetic and structural properties Al-based alloys obtained by mechanical alloying - RODBARI, Reza Jamshidi (2016)
The quasicrystalline alloy which contains the element aluminum present dispersion of particles in nanometric scale that exhibit high values of mechanical strength at room temperatures and high temperatures. The quasicrystalline solids have no crystallographic conventional symmetrical structures; but they are constituted by a unit cell with periodic repetition in space and ordination mode, intermediate between periodic phases and crystalline phases amorphous non-crystalline. The process of Mechanical alloying, a technique of powder metallurgy developed in the 60's, it was established as a viable processing method in the solid state to produce various quasicrystalline phases metastable and stable. The interest in obtaining this material is due to its good structural, electronic and magnetic properties, and the interactions between the properties. In general, the quasicrystalline alloy show resistant to friction and wear, good electrical and thermal insulators, are hard, used in photonic sensors and some formations of quasicrystals are good hydrogen storers. In this work, researched he used the Mechanical alloying to obtain the icosahedral and decagonal phases Al65Mn22Cu13 and Al67,6Cr23,3Fe9,1 in order to study the magnetic properties. Samples of quasicrystalline alloys were obtained by high energy milling with balls mass ratio of 20: 1 with rotation of 200rpm, at time intervals ranging from 1 hour to 40 hours a planetary ball mill Pulverisette 5 Frittsch. Evaluations of physical characterizations were made by scanning electron microscopy showed a microstructure with nonuniform and large nodules symmetries. The X-ray diffraction provides information about identification of phases resulting from Al65Mn22Cu13 Al67,6Cr23,3Fe9,1 and alloys, the formation of icosahedral phases, intermetallic and decagonal and the presence of typical diffraction pattern peaks of their crystallographic network. The magnetic measurements were performed as a function of temperature M (T), and also due to the applied field F (M). It can be concluded that the formation of quasicrystalline phases is possible as grinding time and speed for Al65Mn22Cu13 Al67,6Cr23,3Fe9,1 and alloys obtained by Mechanical alloying process.